The Factors Influencing Financial Donations among Thai Individuals: Impulsive Donation and Deliberative Donation - Khongkaew, Panita; Amonhaemanon, Dalina; Duangmanee, Krittiya (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This research aimed to examine the factors influencing donation decision making among Thai individuals in Generation X and Generation Y. The objective was to compare two types of financial donation behavior: 1) Making an on-the-spot decision to donate upon encountering a donation request (unplanned) and 2) Making an intentional and pre-planned donation. Data were collected through questionnaires and a total of 458 sets of responses were analyzed using logistic regression. The study findings indicated that females had a lower likelihood of making unplanned donation decisions compared to males. Additionally, individuals from Generation Y have a lower likelihood of making donation decisions when faced with a solicitation compared to those from Generation X. The study highlights that individuals who donate money through donation boxes often engage in unplanned donations whereas those who donate money through banking applications or cash accounts are typically individuals who have planned or intended to donate in advance. Furthermore, if individuals are aware that donating money through electronic donation systems can lead to tax deductions, there is an increased likelihood of deciding to donate money, even without prior planning. An interesting point from this study is that individuals with higher incomes and those who frequently donate upon encountering a donation box are more likely to donate, even without prior planning. Therefore, non-profit organizations can apply the findings of this study to formulate marketing strategies. Additionally, the government sector can utilize these findings to develop policies that stimulate and encourage individuals to have a greater inclination to donate, thereby increasing government revenue and alleviating fiscal burdens in alternative ways.